2011
DOI: 10.1111/j.1469-8137.2011.03936.x
|View full text |Cite
|
Sign up to set email alerts
|

A new system for fast and quantitative analysis of heterologous gene expression in plants

Abstract: Summary• Large-scale analysis of transcription factor-cis-acting element interactions in plants, or the dissection of complex transcriptional regulatory mechanisms, requires rapid, robust and reliable systems for the quantification of gene expression.• Here, we describe a new system for transient expression analysis of transcription factors, which takes advantage of the fast and easy production and transfection of Physcomitrella patens protoplasts, coupled to flow cytometry quantification of a fluorescent prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 31 publications
0
72
1
Order By: Relevance
“…S3). We tested the activation of the At3g08900 promoter by ZOU, ICE1 or SCRM-D and by combinations of ZOU with ICE or SCRM-D in a Physcomitrella patens protoplast system (Thévenin et al, 2012), and confirmed that only combinations of ZOU with ICE or SCRM-D could activate promoter activity to levels above background (supplementary material Fig. S3).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…S3). We tested the activation of the At3g08900 promoter by ZOU, ICE1 or SCRM-D and by combinations of ZOU with ICE or SCRM-D in a Physcomitrella patens protoplast system (Thévenin et al, 2012), and confirmed that only combinations of ZOU with ICE or SCRM-D could activate promoter activity to levels above background (supplementary material Fig. S3).…”
Section: Resultsmentioning
confidence: 94%
“…Moss culture, protoplast preparation, vector pBS TPp-A and -B recombination, protoplast transformation and flow cytometry measurement were carried out as described (Thévenin et al, 2012) (see supplementary material Fig. S3).…”
Section: Physcomitrella Protoplast Assaymentioning
confidence: 99%
“…For promoter transactivation assays, Arabidopsis protoplasts were prepared from cell cultures by a sucrose gradient after 3 h of cell wall digestion as in Thomine et al 39 polyethylene glycol (PEG)-mediated transfection was performed using 10 mg of plasmid DNA. Plasmids were obtained from M. Lepetit (pNRT2.1:LUC) 21 and from B. Dubreucq (pACT:LEC2) 40 . The p35S:NLP7 construct was obtained by subcloning into pBS 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Promoters previously cloned into the pDONR207 entry vector (see above) were transferred into the destination vector pBS TPp-B (Thévenin et al, 2012) by LR recombination.…”
Section: Construction Of the Proodd:gfp And Probccp2:gfp Transgenesmentioning
confidence: 99%